2009
DOI: 10.1523/jneurosci.4605-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Axial Diffusivity Is the Primary Correlate of Axonal Injury in the Experimental Autoimmune Encephalomyelitis Spinal Cord: A Quantitative Pixelwise Analysis

Abstract: The dissociation between magnetic resonance imaging (MRI) and permanent disability in multiple sclerosis (MS), termed the clinicoradiological paradox, can primarily be attributed to the lack of specificity of conventional, relaxivity-based MRI measurements in detecting axonal damage, the primary pathological correlate of long-term impairment in MS. Diffusion tensor imaging (DTI) has shown promise in specifically detecting axonal damage and demyelination in MS and its animal model, experimental autoimmune encep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
369
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(397 citation statements)
references
References 49 publications
23
369
5
Order By: Relevance
“…It has been shown that axial diffusivity is highly correlated with axonal damage in EAE mice (DeBoy et al, 2007;Budde et al, 2008) and mouse models of other white matter injuries (Sun et al, 2006;Kim et al, 2007;Mac Donald et al, 2007) resulting from the loss of coherent organization of the axon. Decreased axial diffusivity has been associated with axonal swelling (Song et al 2005), Wallerian degeneration (Song et al 2003), diffuse axonal injury (Arfanakis et al 2002) or axonal integrity/neurofilament dysfunction (positive SMI-32 staining) (Budde et al, 2009;Sun et al 2006). We attribute the strongly reduced λ║ values to axonal damage, which has been demonstrated by marker analysis for axonal impairment and disorganization, as well as morphological findings typical for axonal defects (Pohl et al, 2011) in regions affected by oligodendrocyte cell death.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It has been shown that axial diffusivity is highly correlated with axonal damage in EAE mice (DeBoy et al, 2007;Budde et al, 2008) and mouse models of other white matter injuries (Sun et al, 2006;Kim et al, 2007;Mac Donald et al, 2007) resulting from the loss of coherent organization of the axon. Decreased axial diffusivity has been associated with axonal swelling (Song et al 2005), Wallerian degeneration (Song et al 2003), diffuse axonal injury (Arfanakis et al 2002) or axonal integrity/neurofilament dysfunction (positive SMI-32 staining) (Budde et al, 2009;Sun et al 2006). We attribute the strongly reduced λ║ values to axonal damage, which has been demonstrated by marker analysis for axonal impairment and disorganization, as well as morphological findings typical for axonal defects (Pohl et al, 2011) in regions affected by oligodendrocyte cell death.…”
Section: Discussionmentioning
confidence: 75%
“…These models display disseminated and variable focal lesions at brain or spinal cord level (for review see Lassmann, 2008), which are difficult to interpret when using conventional T1-and T2-weighted MRI techniques sensitive for inflammatory processes only (Nessler et al, 2007;Serres et al, 2009). Therefore, in parallel to the clinical situation both DTI and MTR measures are currently being investigated as measures of demyelination, axonal damage or myelin integrity in EAE (Budde et al, 2008;Budde et al, 2009;DeBoy et al, 2007;Serres et al, 2009;Rausch et al, 2003;Rausch et al, 2009) and CNS demyelination and remyelination in a mouse model of cuprizone-mediated demyelination (Sun et al, 2006;Zaaraoui et al, 2008). Furthermore, the use of ultra-small particles of iron oxide (USPIOs) to visualize macrophage infiltration has been proposed as refined marker for inflammatory events in MS and animal models thereof (Dousset et al, 1999a;Rausch et al, 2003;Floris et al, 2004;Berger et al, 2006;Brochet et al, 2006;Ladewig et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion-weighted images were then co-registered to the anatomical 3D magnetization prepared rapid acquisition of gradient echo (MPRAGE), and fluid attenuated inversion recovery (FLAIR) images using FLIRT (FMRIB's Linear Registration Tool) (Jenkinson et al, 2002). The DTI maps of fractional anisotropy, axial diffusivity ( k ), and radial diffusivity ( o ), were computed using an in-house developed algorithm described previously (Budde et al, 2009). Highresolution 1 Â 1 Â 1 mm 3 sagittal FLAIR images were used for multiple sclerosis lesion identification.…”
Section: Mri Of Human Subjectsmentioning
confidence: 99%
“…In the experimental allergic encephalomyelitis model of multiple sclerosis, contrast changes have been observed in conventional anatomic images (Schellenberg et al, 2007), axial diffusivity has been correlated with axonal damage (Budde et al, 2008;Budde et al, 2007;Budde et al, 2009), and decreased quantitative T2 and magnetic transfer values have been shown (McCreary et al, 2009). Numerous studies have also assessed white matter integrity in mouse models of spinal cord injury, using diffusion tensor imaging Kim et al, 2010;Loy et al, 2007;Tu et al, 2010), T1-and T2-weighted imaging (Gonzalez-Lara et al, 2009;Levene et al, 2008;Nishi et al, 2007), and MRM (Bilgen, 2007).…”
Section: Introductionmentioning
confidence: 99%